Strategi Guru PAI Dalam Menumbuhkan Sikap Kritis Terhadap Isu Kontemporer Melalui Kajian Sejarah Kebudayaan Islam Pada Pembelajaran Kelas X Mas Muallimin Univa Medan - Abdul Rahman Ali (AL-Ikhtiar : Jurnal Studi Islam, 2026)
This article explores the strategies of Islamic Religious Education (PAI) teachers in fostering critical thinking in students toward contemporary issues through the study of Islamic Cultural History (ISH) in tenth-grade classes at MAS Muallimin UNIVA Medan. The study employed a descriptive qualitative research approach and Classroom Action Research (CAR) to design, implement, and reflect on critical thinking-oriented teaching strategies. Interventions included the application of inquiry-based learning models, problem-based learning, guided discussions (Socratic questioning), primary source analysis, contemporary issue-based projects, and the use of technology for historical sources. Data were collected through classroom observations, teacher and student interviews, documentation of learning outcomes, and critical thinking assessment instruments. Results indicated improvements in students' analytical skills, source evaluation, and critical disposition toward contemporary issues such as pluralism, social media ethics, and religious moderation. Effective strategies combined historiographic scaffolding, authentic assessment, and teacher-community collaboration. This article presents a set of operational strategies (lesson plans, student worksheets, and critical thinking rubrics) that are feasible for implementation and are recommended for ISH curriculum integration. The novelty of this research is the integrated strategy model that directly links the study of Islamic cultural history with the analysis of contemporary issues for Madrasah Aliyah students Abstrak Artikel ini mengeksplorasi strategi guru Pendidikan Agama Islam (PAI) dalam menumbuhkan sikap kritis siswa terhadap isu-isu kontemporer melalui kajian Sejarah Kebudayaan Islam (SKI) pada pembelajaran kelas X di MAS Muallimin UNIVA Medan. Penelitian menggunakan pendekatan penelitian kualitatif deskriptif dan Penelitian Tindakan Kelas (PTK) untuk merancang, menerapkan, dan merefleksikan strategi pengajaran berorientasi keterampilan berpikir kritis. Intervensi meliputi penerapan model pembelajaran inquiry-based learning, problem-based learning, diskusi terarah (Socratic questioning), analisis sumber primer, proyek berbasis isu kontemporer, dan pemanfaatan teknologi untuk sumber-sumber historis. Data dikumpulkan melalui observasi kelas, wawancara guru dan siswa, dokumentasi produk belajar, serta instrumen penilaian berpikir kritis. Hasil menunjukkan peningkatan kemampuan analisis, evaluasi sumber, dan kecenderungan kritis siswa terhadap isu kontemporer seperti pluralisme, etika media sosial, dan moderasi beragama. Strategi efektif menggabungkan scaffolding historiografis, penilaian autentik, dan kolaborasi guru–komunitas. Artikel ini menyajikan perangkat strategi operasional (rencana pembelajaran, LKPD, rubrik berpikir kritis) yang layak implementasi dan direkomendasikan untuk integrasi kurikulum SKI. Kebaruan penelitian adalah model strategi terpadu yang mengaitkan kajian sejarah kebudayaan Islam secara langsung dengan analisis isu kontemporer bagi siswa madrasah Aliyah